2017
DOI: 10.1155/2017/3017837
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Behavioral Pain Cues: Implicit Automaticity and Control Dimensions in Observational Measures

Abstract: Some pain behaviors appear to be automatic, reflexive manifestations of pain, whereas others present as voluntarily controlled. This project examined whether this distinction would characterize pain cues used in observational pain measures for children aged 4–12. To develop a comprehensive list of cues, a systematic literature search of studies describing development of children's observational pain assessment tools was conducted using MEDLINE, PsycINFO, and Web of Science. Twenty-one articles satisfied the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Pediatric pain management includes pain recognition to the moment when the professional defines which strategies to use to relieve it. For this sequence of events to be carried out properly, the nursing professional needs to understand the importance of his/her role in this process and recognize how prepared he/she is to carry out this management 14 . This preparedness is evidenced in the SCMP as the professional training involved in the professional's intrapersonal factors, which in practice is illustrated as transmitted content, institutional training, and previous knowledge 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric pain management includes pain recognition to the moment when the professional defines which strategies to use to relieve it. For this sequence of events to be carried out properly, the nursing professional needs to understand the importance of his/her role in this process and recognize how prepared he/she is to carry out this management 14 . This preparedness is evidenced in the SCMP as the professional training involved in the professional's intrapersonal factors, which in practice is illustrated as transmitted content, institutional training, and previous knowledge 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In fragile group with advanced stage of dementia (PACSLAC, DOLOPLUS2, PAINAD) [29,32,33,36,39,44,58] and for a cognitive impaired [46,47]. For unconscious patients using observational scales such as (BPS, CPOT, and NVPS) [28,45,48,55,59]. A significant amount of previous knowledge and experience is necessary to adjust the accurately.…”
Section: Observation Al Scalementioning
confidence: 99%
“…Further, infants, young children, and others with communication/neurological disabilities do not have the ability or capacity to self-report pain levels [3,5,6]. As a result, to evaluate pain in populations with communication limitations, observational tools based on nonverbal indicators associated with pain have been developed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of the various modalities of nonverbal expression (e.g., bodily movement, vocal qualities of speech), it has been suggested that facial activity provides the most sensitive, specific, and accessible information about the presence, nature, and severity of pain across the life span, from infancy [8] to advanced age [9]. Moreover, observers largely consider facial activity during painful events to be a relatively spontaneous reaction [7].…”
Section: Introductionmentioning
confidence: 99%